Intergrasi Masjid Raya Syahabuddin di Siak Sebagai Sejarah Lokal Riau Dalam Pembelajaran Sejarah Kelas X - Rizki Ananda Hasibuan; Asyrul Fikri; Piki Setri Pernantah (Journal on Education, 2023)
History as a reconstruction of the past is expected to be able to rebuild past memories for the present and the future. Local history is part of national history whose scope is limited to a certain area. One example of local historical heritage that can be utilized in learning in the classroom is integrating heritage in Siak, namely the Syahbuddin Great Mosque which was founded in 1882 by the Siak Sultanate, namely Sultan Syarif Kasim I. The purpose of this writing is to reflect on historical material during the Islamic period in the learning process history so that the teacher can use it as a facilitator in the classroom to preserve the culture that exists in the area where we live. The method used in carrying out this research is descriptive qualitative with literature study